2015
DOI: 10.1007/s12032-015-0545-7
|View full text |Cite
|
Sign up to set email alerts
|

PinX1 inhibits cell proliferation, migration and invasion in glioma cells

Abstract: PinX1 induces apoptosis and suppresses cell proliferation in some cancer cells, and the expression of PinX1 is frequently decreased in some cancer and negatively associated with metastasis and prognosis. However, the precise roles of PinX1 in gliomas have not been studied. In this study, we found that PinX1 obviously reduced the gliomas cell proliferation through regulating the expressions of cell cycle-relative molecules to arrest cell at G1 phase and down-regulating the expression of component telomerase rev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
6
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 29 publications
2
6
0
Order By: Relevance
“…In addition to the well-known effects of this pentacyclic acridine compound, here we report also its remarkable ability to upregulate the telomerase inhibitor PINX1, which has been recently reported as a suppressive gene in glioma through its ability to repress telomerase activity and cell invasion and migration [54]. Among NDIs, C2 was the most interesting agent, able to induce moderate telomere dysfunction, Bcl2 downregulation, ATR-CHK1 DNA damage response, cell cycle slowdown in S-phase coupled with PCC and apoptosis.…”
Section: Discussionsupporting
confidence: 56%
“…In addition to the well-known effects of this pentacyclic acridine compound, here we report also its remarkable ability to upregulate the telomerase inhibitor PINX1, which has been recently reported as a suppressive gene in glioma through its ability to repress telomerase activity and cell invasion and migration [54]. Among NDIs, C2 was the most interesting agent, able to induce moderate telomere dysfunction, Bcl2 downregulation, ATR-CHK1 DNA damage response, cell cycle slowdown in S-phase coupled with PCC and apoptosis.…”
Section: Discussionsupporting
confidence: 56%
“…It has been reported that PinX1 suppress tumor growth and depletion of endogenous PinX1 enhanced tumorigenicity [32]. We observed that knockdown of PinX1 could also enhance cell proliferation and clonogenicity of NSCLC cell lines in vitro.…”
Section: Discussionmentioning
confidence: 51%
“…In the central nervous system, matrix metalloproteinases play a key role in cleaving the BBB, such that an increase in matrix metalloproteinase expression results in increased BBB permeability . Furthermore, in vitro studies have demonstrated a role for TERT in matrix metalloproteinase regulation in gliomas …”
Section: Discussionmentioning
confidence: 99%
“…23 Furthermore, in vitro studies have demonstrated a role for TERT in matrix metalloproteinase regulation in gliomas. 24 In addition to telomere preservation, TERT has been shown to upregulate matrix metalloproteinases, which are known to target the BBB. We, therefore, sought to evaluate BBB dysfunction in GBM in the context of TERT mutation.…”
Section: Discussionmentioning
confidence: 99%